A BRIEF STUDY OF RAJA MAHENDRA PRATAP SINGH: HIS PHILOSOPHIES AND IDEAS FOR SOCIAL REFORM - Prakash, Tarun; Kumar, Hradayesh (International Journal of Research -GRANTHAALAYAH, 2025)
This study explores the multifaceted life and legacy of Raja Mahendra Pratap Singh, a visionary leader whose contributions to India’s early 20th-century socio-political and religious landscape remain underrecognized. Born into royalty, Singh defied privilege by dedicating his life to uplifting the oppressed through education, land reform, and the eradication of untouchability. His progressive social philosophy emphasized education as a tool of empowerment, particularly for marginalized communities, and inspired systemic changes in access and policy. Influenced by the Arya Samaj, his religious outlook merged monotheistic reformist ideals with an unwavering commitment to pluralism and interfaith harmony. Raja Mahendra Pratap’s rejection of idol worship, promotion of Vedic values, and advocacy for religious inclusivity positioned him as both a spiritual reformer and a unifying figure in a deeply divided society.